Taxonomic notes on the genus Alphonsea (Annonaceae) in Thailand - Leeratiwong, Charan; Chalermglin, Piya; Johnson, David (Thai Forest Bulletin (Botany), 2020)
The following four species in the genus Alphonsea (Annonaceae) are new records for Thailand: Alphonsea glandulosa, A. kingii, A. lucida and A. malayana. Alphonsea lutea var. longipes is reduced to a taxonomic synonym of A. glandulosa. The reinstatement of A. pallida is proposed and explained. Complete descriptions are provided here for both A. pallida and A. siamensis following the recent discovery of the fruits of the former and the flowers of the latter. Descriptions of all taxa with notes on their distribution, ecology, vernacular names and photographs are also provided.